The Effectivenes of Technopreneurship with Cooperative Learning for Technopreneur in SMK (CLTSMK) - et. al., Moch. Bruri Triyono, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to reveal: 1) effectiveness of technopreneurshipin SMK for the survival skills of students, 2) aspects of motivation to learn, 3) aspects of thinking creativy, and 4) aspects of the student’s managerial of class XI students majoring in Mechanical Light Vehicle on the competence of the electrical system at SMKN 2 Depok and SMK Muhammadiyah 1 Playen. This research is a quasi experimental. The study design refers to the model developed by Donald Ary et.al. This study consisted of classroom control using conventional teaching methods and classroom experiments using model CLTSMK. The results of the research are as follows: (1) Application of CLTSMK effective learning model for the development of survival skills students (2) Aspects of motivation to learn of the control A the qualification "Less" while the experimental class the qualification "Very Good". motivation to learn the control class B the qualification "Enough" while the experimental class the qualification "Very Good". (3) Aspects of thinking creativity of the control class A the qualification "Enough" while the experimental class the qualification "Very Good". Thinking creativity of the control class B the qualification "Enough" while the experimental class the qualification "Very Good". (4) Aspects of student’s managerial in the control class Athe qualification "Enough" while the experimental class the qualification "Very Good". Student’s managerial in the control class B the qualification "Enough" while the experimental class the qualification "Very Good".